“Task-based language teaching in English learning-teaching process applied in 10th grade students at the Miguel Iturralde Military Academy ii” - Caiza Marcalla, Allison Andrea (2022)
The Task-Based Language Teaching approach responds to a learning approach of a language that is based on performing tasks. This approach presents a proposal in which students must perform a series of tasks in a language of interest to learn, so it is also developed the skill of communication. At the Military Academy Miguel Iturralde II, the students of the 10th grade, class "A" present different problems to establish a communication between the classmates and even the teacher; Thus, the application of an approach that helps students develop their communication skills is necessary, in addition to obtaining significant learning. Thus, this research is directed to analyze the influence of the Task-Based Language Teaching approach in the students of the 10th grade class A, during the teaching-learning process. The participants of this project were chosen after a heading of prior observation, as well as the teacher was considered. The mixed approach was used to jointly analyze both qualitative and quantitative data since an understanding of the separate research problem is required, thus obtaining a much more detailed result. The data analysis suggested that the Task-Based Language Teaching approach is a viable approach to the development of a significant teaching-learning process respect to the English language, since it allows a development of communicative skills, as well as a better Interaction between classmates. It can be said that if the approach Task-Based Language Teaching is applied in English classes for a better teaching-learning process it would be beneficial for the group of students since the task solution using the English language is an effective way to expose learners to the foreign language and thus obtaining a significant learning.